Glucocorticoids Disrupt Skeletal Angiogenesis Through Transrepression of NF‐κB–Mediated Preosteoclast Pdgfb Transcription in Young Mice. (11th March 2020) - Peng, Yi; Lv, Shan; Li, Yusheng; Zhu, Jianxi; Chen, Shijie; Zhen, Gehua; Cao, Xu; Wu, Song; Crane, Janet L.
ABSTRACT: In the growing skeleton, angiogenesis is intimately coupled with osteogenesis. Chronic, high doses of glucocorticoids (GCs) are associated with decreased bone vasculature and induce osteoporosis and growth failure. The mechanism of GC‐suppression of angiogenesis and relationship to osteoporosis and growth retardation remains largely unknown. Type H vessels, which are regulated by preosteoclast (POC) platelet‐derived growth factor–BB (PDGF‐BB), are specifically coupled with bone formation and development. We determined the effect of GCs on POC synthesis of PDGF‐BB in relation to type H vessel formation, bone mass, and bone growth in the distal femur of 2‐week‐old young mice receiving prednisolone or vehicle for 2, 4, or 6 weeks. After 2 weeks of prednisolone, the number of POCs were unchanged while POC synthesis of PDGF‐BB was reduced. Longer treatment with prednisolone reduced POCs numbers and PDGF‐BB. These changes were associated with a reduction in type H vessels, bone formation rate, bone mass, and bone length at each time point. In vitro, excessive concentrations of prednisolone (10 −6 M) resulted in decreased PDGF‐BB concentration and POC numbers. Conditioned medium from POC cultures treated with control concentration of prednisolone (10 −7 M) or recombinant PDGF‐BB stimulated endothelial tube formation, whereas conditioned medium from control concentration of prednisolone‐treated POC cultures neutralized by PDGF‐BB antibody or excessive prednisolone inhibited endothelial tube formation. Administration of excessive prednisolone attenuated the P65 subunit of nuclear factor kappa B (NF‐κB) binding to the Pdgfb promoter, resulting in lower Pdgfb transcription. Co‐treatment with excessive prednisolone and the glucocorticoid receptor (GR) antagonist (RU486), GR siRNA, or TNFα rescued NF‐κB binding to the Pdgfb promoter and endothelial tube formation. These results indicate that PDGF‐BB synthesis in POCs is suppressed by GCs through transrepression of GR/NF‐κB, thus inhibiting type H vessel formation and associated osteoporosis and growth failure. © 2020 American Society for Bone and Mineral Research.